Neurodevelopmental outcomes at 3 years old for infants with birth weights under 500 g - Syunsuke Nagara; Masanori Kouwaki; Takao Togawa; Tokio Sugiura; Mayumi Okada; Norihisa Koyama (Pediatrics and Neonatology)
Marked improvements have been achieved in the survival of extremely low birth weight infants, but survival rates and prognoses of extremely small infants with birth weights ≤500 g remain poor. The aim of this study was to clarify long-term outcomes for surviving infants with birth weights ≤500 g. Methods: The study population comprised fetuses of gestational age ≥22 weeks, expected live- or stillbirth weight ≤500 g, and birth date between 2003 and 2012. Developmental assessments were performed prospectively at 3 years old. Results: Data were obtained for 21 fetuses, including 10 live births and 11 stillbirths. Of the 10 live births, median gestational age was 25.2 weeks (range, 22.4–27.1 weeks), median birth weight was 426 g (range, 370–483 g), and two neonates died before discharge. One infant with severe asphyxia died within 12 h and another infant with Down syndrome died at 34 days. The survival rate was thus 80%. All surviving infants were small for gestational age. Seven of the 8 surviving infants (88%) weighed less than 2500 g at a corrected age of 40 weeks. Seven infants were available for developmental assessments at 3 years old. One infant could not be followed. Two of those seven infants (29%) showed normal development, three infants (42%) showed mild neurodevelopmental disability, and two infants (29%) showed severe neurodevelopmental disability. One infant had periventricular leukomalacia and cerebral palsy. Two of the seven infants (29%) had short stature (<3 SD) at 3 years old. Conclusion: Although the survival rate among live births was good (80%) in this study, neurodevelopmental outcomes remained poor in infants with birth weights ≤500 g. Further large studies are needed to assess long-term outcomes for extremely small infants.